β-arrestin 2 Is a Prognostic Factor for Survival of Ovarian Cancer Patients Upregulating Cell Proliferation - Czogalla, Bastian; Partenheimer, Alexandra; Jeschke, Udo; von Schönfeldt, Viktoria; Mayr, Doris; Mahner, Sven; Burges, Alexander; Simoni, Manuela; Melli, Beatrice; Benevelli, Riccardo; Bertini, Sara; Casarini, Livio; et al. (Frontiers in Endocrinology, 2020)
Establishing reliable prognostic factors as well as specific targets for new therapeutic approaches is an urgent requirement in advanced ovarian cancer. For several tumor entities, the ubiquitously spread scaffold protein β-arrestin 2, a multifunctional scaffold protein regulating signal transduction and internalization of activated G protein-coupled receptors (GPCRs), has been considered with rising interest for carcinogenesis. Therefore, we aimed to elucidate the prognostic impact of β-arrestin 2 and its functional role in ovarian cancer. β-arrestin 2 expression was analyzed in a subset of 156 samples of ovarian cancer patients by immunohistochemistry. Cytoplasmic expression levels were correlated with clinical as well as pathological characteristics and with prognosis. The biologic impact of β-arrestin 2 on cell proliferation and survival was evaluated, in vitro. Following transient transfection by increasing concentrations of plasmid encoding β-arrestin 2, immortalized cell lines were evaluated in cell viability and death. β-arrestin 2 was detected in all histological ovarian cancer subtypes with highest intensity in clear cell histology. High β-arrestin 2 expression levels correlated with high-grade serous histology and the expression of the gonadotropin receptors FSHR and LHCGR, as well as the membrane estrogen receptor GPER and hCGβ. Higher cytoplasmic β-arrestin 2 expression was associated with a significantly impaired prognosis (median 29.88 vs 50.64 months; P=0.025). Clinical data were confirmed in transfected HEK293 cells and human immortalized granulosa cell line (hGL5) in vitro, where the induction of β-arrestin 2 cDNA expression enhanced cell viability, while the depletion of the molecule by siRNA resulted in cell death. Reflecting the role of β-arrestin 2 in modulating GPCR-induced proliferative and anti-apoptotic signals, we propose β-arrestin 2 as an important prognostic factor and also as a promising target for new therapeutic approaches in advanced ovarian cancer.